2021
DOI: 10.1101/2021.06.30.21259731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA methylome-wide association study of genetic risk for depression implicates antigen processing and immune responses

Abstract: Background: Depression is a disabling and highly prevalent condition where genetic and epigenetic differences, such as DNA methylation (DNAm), contribute to prediction of disease liability. Method: We investigated the association between polygenic risk scores (PRS) for depression and DNAm by conducting a methylome-wide association study (MWAS) in Generation Scotland (N=8,898, mean age=49.8 years) with replication in the Lothian Birth Cohorts of 1921 and 1936 and adults in Avon Longitudinal Study of Parents an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Furthermore, in two other open-access cohorts, this locus demonstrated a clear statistical tendency toward an association with similar phenotypes. We also confirm the association between cg19624444 and depression that has been identified previously [41]. Additionally, we investigated if the discovered CpG sites could be related to the expression of MAD1L1 and stress response.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, in two other open-access cohorts, this locus demonstrated a clear statistical tendency toward an association with similar phenotypes. We also confirm the association between cg19624444 and depression that has been identified previously [41]. Additionally, we investigated if the discovered CpG sites could be related to the expression of MAD1L1 and stress response.…”
Section: Introductionsupporting
confidence: 86%
“…However, a recent study by Shen et al identified cg19624444 as a depression-related methylation site that was associated with a depression polygenic risk score. This CpG has also shown casual associations based on Mendelian randomization analysis conducted in the same study [41]. Our SNP-CpG analysis with limma identified cg19624444 as a top hit based on adolescent cohorts at screening and recall using a dominant genetic model.…”
Section: Discussionmentioning
confidence: 63%
“…Our principal investigator, Gerd Schulte-Körne, can be approached by interested parties for further discussion and can be reached at Gerd.Schulte-Koerne(at)med.uni-muenchen.de; the corresponding author is available at Aline.Scherff(at)med.uni-muenchen.de. The BioMD-Y sample has most recently been used as part of a large MD MWAS study (Shen et al 92, in preparation) and is open to contributing to further large consortium studies addressing particularly those aspects mentioned above requiring larger data sets. It is hoped that through explicitly testing novel gene–environment hypotheses as well as replicating findings known from adult literature, BioMD-Y will inform clinical practice, prevention and treatment of depression in children and adolescents by providing a factual basis for more tailored approaches to hitherto assumed commonalities and differences.…”
Section: Collaborations and Future Directionsmentioning
confidence: 99%
“…Detailed information related to sample processing, methylation data generation and quality control for MMNP 18 , PMMST 18 , ENID 71 , and ALSPAC [75][76][77] have been previously published. We provide some further brief details below.…”
Section: Dna Methylation Profiling and Data Processingmentioning
confidence: 99%